2019
DOI: 10.1167/iovs.18-26248
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits Wound Healing and Lens Fibrosis: A Putative Candidate for Posterior Capsule Opacification Prevention

Abstract: PURPOSE. Posterior capsule opacification (PCO) is a common complication of cataract surgery. In addition to improved surgical methods and IOL designs, it is likely additional agents will be needed to improve patient outcomes. Presently no pharmacological agent is in clinical use to prevent PCO. Here we investigate the putative ability of resveratrol (RESV), a naturally occurring polyphenol, as a therapeutic agent. METHODS. The human lens epithelial cell line FHL124, a human lens capsular bag model, and central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…Our findings identified that Snail1 and Zeb1 are involved in the pathogenesis of PCO. Additionally, it is known that TGF-β2-induced EMT plays a pivotal role in PCO progression [7,8,42]. We found that NEAT1 knockdown suppressed Snail1 expression induced by TGF-β2 and miR-34a overexpression enhanced these effects in primary HLECs.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Our findings identified that Snail1 and Zeb1 are involved in the pathogenesis of PCO. Additionally, it is known that TGF-β2-induced EMT plays a pivotal role in PCO progression [7,8,42]. We found that NEAT1 knockdown suppressed Snail1 expression induced by TGF-β2 and miR-34a overexpression enhanced these effects in primary HLECs.…”
mentioning
confidence: 66%
“…Based on the results, we hypothesized NEAT1 contributes to the pathogenesis of PCO. The previous studies have revealed that TGF-β2 is a pivotal inducer of EMT-related changes in PCO [7][8][9][10]. Hence, we explored whether TGF-β2 induces downregulation of epithelial differentiation markers (i.e., E-cadherin) and upregulation of mesenchymal cell markers (i.e., fibronectin) in primary HLECs through a NEAT1-dependent mechanism.…”
Section: Tgf-β2 Induces Overexpression Of Emt Markers In Primary Lecsmentioning
confidence: 98%
See 1 more Smart Citation
“…Using this system growth, EMT and differentiation have been observed and thus epithelial explants are a tractable system for the study of PCO (Gordon-Thomson et al, 1998;Mansfield et al, 2004;McAvoy and Chamberlain, 1989). Explant cultures can also be established from human lenses (Maidment et al, 2004;Shu and Lovicu, 2017;Smith et al, 2019;Weatherbee et al, 2019). To date, growth, EMT, increased matrix production and contraction have been studied, but differentiation is yet to be observed.…”
Section: In Vivo Animal Modelsmentioning
confidence: 99%
“…Resveratrol, one of the natural polyphenols, has the function of inhibiting fibrosis and antioxidants. Smith et al [37] added 30 μmol/L resveratrol into human LECs in vitro, and the results of quantitative real-time PCR showed that resveratrol could decrease the level of not only EMT markers, α-SMA and fibronectins, but also TGF-β activator, matrix metalloproteinase (MMP) 2. is study explained that resveratrol was more likely to prevent lens capsule opacification via hindering LECs' EMT, but they did not observe and evaluate the effect of resveratrol on other intraocular tissue cells. While Resveratrol has been authorized to the market, it is usually used as a nutrient supplement to improve bone density and protect the cardiovascular system, and further research that elaborates its pharmacologic mechanism is still in need.…”
Section: Other Medicines On Lecs' Emtmentioning
confidence: 99%